Effect of Danlu capsules for the treatment of breast hyperplasia with mastalgia: a multicenter, double-blind, randomized controlled trial protocol - Guo, Qianqian; Luo, Ziqian; Huang, Jihan; Xu, Rui; Dai, Yan; Chen, Qianjun (Frontiers in Medicine, 2025)
BackgroundMastalgia is a prevalent condition among women. Conservative treatment is initially recommended, and tamoxifen is considered a second-line option, but it can cause menopausal-like symptoms. Chinese patent medications are proposed as alternatives, yet evidence remains insufficient. Danlu capsules, which are recommended in certain clinical practice guidelines for breast hyperplasia in China, have demonstrated therapeutic effects on breast pain. However, high-quality randomized controlled trials are lacking to clarify Danlu capsules’ efficacy in treating breast pain. This study aims to examine the effectiveness and safety of Danlu capsules for the treatment of mastalgia.MethodsThis study is a multicenter, randomized, double-blind, placebo-controlled, and superiority clinical trial involving 264 participants, which will be randomly assigned in a 1:1 ratio to either receive Danlu capsule or placebo via a centralized system. All participants will undergo an eight-week treatment period and an additional 4 weeks of follow-up. The primary outcome will be the breast pain assessed using the visual analog scale (VAS). Secondary outcomes will include the evaluation of the quality-of-life questionnaire, the self-rating anxiety questionnaire, and the self-rating depression questionnaire. Safety monitoring and adverse event recording will be implemented throughout the study. Efficacy will be assessed through covariance analysis for primary endpoints and t-tests for secondary outcomes, with mixed models for repeated measures comparing breast pain VAS score changes at weeks 4, 8, and 12. All statistical analyses will be conducted using SAS (9.4), and no interim analyses will be performed.DiscussionThis trial will evaluate the clinical efficacy and safety of Danlu capsules in treating breast hyperplasia with mastalgia. The findings are expected to provide an evidence-based treatment option supporting the potential role of Chinese patent medicine in the management of breast pain.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, ITMCTR2025000715.